Indonesia - Prasetya, Nur Wachid Adi; Linda Perdana Wanti; Lina Puspitasari; Indonesia (P3M Politeknik Negeri Cilacap, 2023)
Preeclampsia is a disease of pregnant women, causing many complaints, including dizziness. Massage is the right solution to reduce dizziness since the use of analgesic drugs is not recommended. Submission of massage information can be more effective through digital technology. The purpose of this research is to build an application based on Augmented Reality (AR) as a guide for facial massage movements for midwives and pregnant women to deal with complaints of dizziness for pregnant women. The method used is the Multimedia Development Life Cycle (MDLC), which consists of the stages of making a concept, making a design, collecting materials, combining materials, testing, and distribution. Black box testing on 10 scenarios produces a value of 100%, which means the application can run properly. In addition, usability testing using the System Usabilities Scale (SUS) method shows a value of 69.5, which means that the application has the